Settler Colonial Intrusion, Tasmanian Tiger Extinction, and Animal Privacy in Walton Ford’s The Undead - Whittle, Matthew (Privacy Studies Journal, 2026)
This article examines the role of contemporary visual art in contributing to privacy studies debates about the ethics of looking at animal suffering. Concentrating on Walton Ford’s painting The Undead (2008), it expands these debates—which have focused on images of animal captivity in zoos and slaughterhouses—to include the connections between species extinction and settler colonial intrusion. It reveals that the artwork satirizes illustrations that solidified the Tasmanian tiger’s status as a threat to livestock for settler colonialists. Placing The Undead in comparison with documentary footage of Tasmanian tigers in zoos and farmed sheep in abattoirs, the article goes on to explore how images of caged and malnourished Tasmanian tigers have secured the animal’s place in conservation discourse while the mistreatment of sheep is concealed. Reflecting on the private/public dichotomy, the article adopts a terminology of active non-publicity to name this concealment. It concludes by demonstrating that a commensurate concealment is evident in the lack of attention paid to the genocide of Aboriginal Tasmanians. In exploring the non-human and human costs of settler colonial intrusion, the article argues for creative portrayals of suffering that can signal attention to the histories and legacies of European colonialism without violating animal privacy.